Seni Mendengar Konselor dalam Komunikasi Konseling - Noibe Halawa; Famahato Lase (Journal on Education, 2024)
Counselors need to have good listening skills in the counseling communication process, and these abilities have different levels, from the lowest to the highest. The aim of this research is to solve problems regarding: types and levels of listening, counselors as good listeners and their intensive listening skills in the counseling communication process, their grip when listening and speaking, the requirements for being a good listener, and the obstacles. This research uses a qualitative literature study method, the research instrument is the researcher himself, data is collected from the source using library study techniques, and analyzed qualitatively using content analysis. The results of the study revealed that: (1) there are four levels of listening skills in the counseling communication process, namely listening level: one is non-listener, two is shallow listener, three is evaluative listener, and level four is active listener and only this kind of listening can be used in the communication process counseling; (2) five ways for a counselor to be a good listener, namely: listening attentively, trying to provide appropriate reinforcement so that they are truly together in the conversation, the counselor's sitting posture looks calm and comfortable, and there is eye contact/photograph; (3) counselor skills in listening while understanding; (4) the grip when speaking facilitates the client's conversation; (5) the requirements for being a good listener are trying to: understand the client's feelings, give psychological caress, say his name correctly, give the client as many opportunities as possible to talk about his situation, respect his opinions and ideas, speak honestly and (6) Obstacles in the counseling communication process, namely: motivation and attitudes that do not want to hear things that should be heard, lack of concentration, misunderstanding about the meaning of listening, background experience and education, and prejudice that tends to be difficult to hear.